Gingivitis artefacta – Self injurious behaviour in adult patients of depression Report of 2 cases - Mazumdar, Utpal; Mazumdar, Bipa; Arya MDS, Gaurav; Rajkumar, I.R. (Journal of Orofacial Research, 2011)
Gingivitis artefacta is a type of periodontal disease caused by self-inflicted injuries to the gingival tissues. The injuries, most commonly, occur due to” picking” or scratching of the gingiva with fingernails or any foreign object. Apart from pathological causes of the gums and established habits of nail biting and finger sucking, the aetiology could be psychological problems. We report cases of gingivitis artefacta in two adult patients of a family, who are suffering from depression and anxiety neurosis. Self-injurious behaviour (SIB) is a complex disorder. Management includes both dental correction and psychiatric intervention to allay this disturbing and damaging habit of the patient. Practitioners need to be aware of such presentations in patients.